Activation of HIF-1α/VEGF-A pathway by deferoxamine ameliorates retinal hypoxia in a rat subarachnoid hemorrhage model. Issue 16 (19th September 2022) - Deji, Qu-Zhen; Wang, Xue; Zhaba, Wang-Dui; Deng, Hong-Ji; Han, Yan-Ling; Gao, Sheng-Qing; Liu, Xi-Lin; Zhou, Meng-Liang
Abstract : Background and purpose: Subarachnoid hemorrhage (SAH) is associated with sustained vasoconstriction in retinal vessels and vasoconstriction leads to retinal ischemia and hypoxia. Our previous finding also revealed the changes in hypoxia-related elements in the retina after SAH, further lending weight to the hypothesis that retinal vasospasm and hypoxia after SAH. Deferoxamine is a high-affinity iron chelator with reported neuroprotective effects against stroke. Here, we aimed to explore the effects of deferoxamine on retinal hypoxia after SAH. Methods: SAH was established and deferoxamine was injected intraperitoneally for 3 days in the treatment group. To detect retinal new vessels, platelet endothelial cell adhesion molecule (CD31) was labeled by immunofluorescence and immunohistochemistry. Furthermore, the effects of deferoxamine on the expression of vascular endothelial growth factor A (VEGF-A) and hypoxia-inducible factor-1α (HIF-1α) were revealed by western blot analysis. Results: The immunofluorescence and immunohistochemical staining of CD31 revealed a marked increase in new vessels in the retinal ganglion cell layer after deferoxamine treatment. By western blot analysis, HIF-1α and VEGF-A increased gradually in the first day and then rebounded to a new level on day 7. A deferoxamine-induced increase in HIF-1α/VEGF-A expression was also confirmed by western blot. Conclusions: Our findings suggest that modulating the application of deferoxamine may offer therapeutic approaches to alleviate retinal complications after SAH.